2023
DOI: 10.21037/tcr-23-1175
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the distinct features of metastasis male breast cancer and its effect on overall survival based on the SEER database compared with female breast cancer

Heng Li,
Yong Zhang,
Mei-Sze Teh
et al.

Abstract: Background Male breast cancer (MBC) is a rare disease and differs from female breast cancer (FBC) in clinicopathological and immune tissue types. Given the limited research on MBC due to its rarity, an understanding of the shared and distinct features of MBC and FBC is vital for formulating efficacious treatment strategies. Methods Data of patients diagnosed with metastatic breast cancer in the Surveillance, Epidemiology, and End Results (SEER) database from 2012 to 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Unfortunately, male breast cancer can sometimes be identified late, with lymph node involvement and advanced staging by the time of diagnosis, hence its worse prognosis [ 38 ]. Different studies have shown that the incidence of distant metastases is higher in male breast cancer, when compared to female breast cancer [ 39 , 40 ]. This seems to be related to the lack of knowledge about this disease in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, male breast cancer can sometimes be identified late, with lymph node involvement and advanced staging by the time of diagnosis, hence its worse prognosis [ 38 ]. Different studies have shown that the incidence of distant metastases is higher in male breast cancer, when compared to female breast cancer [ 39 , 40 ]. This seems to be related to the lack of knowledge about this disease in the general population.…”
Section: Discussionmentioning
confidence: 99%